Microporous Carbon Nitride (C3N5.4) with Tetrazine based Molecular Structure for Efficient Adsorption of CO2 and Water. Issue 39 (21st August 2021) - Sathish, CI; Premkumar, S.; Chu, Xueze; Yu, Xiaojiang; Breese, Mark B. H.; Al‐Abri, Mohammed; Al‐Muhtaseb, Ala'a H.; Karakoti, Ajay; Yi, Jiabao; Vinu, Ajayan
Abstract: Mesoporous carbon nitrides with C3 N5 and C3 N6 stoichiometries created a new momentum in the field of organic metal‐free semiconductors owing to their unique band structures and high basicity. Here, we report on the preparation of a novel graphitic microporous carbon nitride with a tetrazine based chemical structure and the composition of C3 N5.4 using ultra‐stable Y zeolite as the template and aminoguanidine hydrochloride, a high nitrogen‐containing molecule, as the CN precursor. Spectroscopic characterization and density functional theory calculations reveal that the prepared material exhibits a new molecular structure, which comprises two tetrazines and one triazine rings in the unit cell and is thermodynamically stable. The resultant carbon nitride shows an outstanding surface area of 130.4 m 2 g −1 and demonstrates excellent CO2 adsorption per unit surface area of 47.54 μmol m −2, which is due to the existence of abundant free NH2 groups, basic sites and microporosity. The material also exhibits highly selective sensing over water molecules (151.1 mmol g −1 ) and aliphatic hydrocarbons due to its unique microporous structure with a high amount of hydrophilic nitrogen moieties and recognizing ability towards small molecules. Abstract : The new class of microporous carbon nitride with rich nitrogen moieties templated from zeolite shows periodic porosity with a unique CN framework and enhanced active sites that triggered highly selective sensing owing to the high amount of hydrophilic nitrogen species.